Stabilisation of acrylic latexes containing silica nanoparticles for dirt repellent coating applications. (10th April 2023) - Swift, T.
Abstract: This study examines the feasibility of using colloidal silica nanoparticles as active agents in high concentration waterborne polymer latex formulations. We showed that distributing the silica throughout the waterborne emulsion formed a composite coating material with a hydrophilic surface that consequently reduced exterior dirt pickup. Two grades of silica nanoparticles were studied, one using sodium stabilisation and another using epoxysilane modification to introduce glycidoxypropyltrimethoxysilane surface functionality. Rheological study of the waterborne latex on mixing showed that there was an immediate pH responsive interaction between the silica sols and the polymer latex. Once loading of sodium charge stabilised silica NPs exceeded the volume required for heteroflocculation to occur the mixture demonstrated the potential to gel on standing – a process which took weeks, or months, to occur depending on the pH and relative concentrations used. At least fifty percent silane modification to the NP surface was found to be necessary to maintain a stable colloidal dispersion for long term storage of the waterborne latex. Despite this both grades of silica were found to imbue reductions in dirt pickup when applied to exterior masonry concrete studies over a 3-month weathering test. Graphical abstract: Image 1 Highlights: Silica nanoparticles can be mixed with high concentration polymer latex solutions to decorate latex surface nut give pH responsive viscosity increase. Storage of non-modified silica NP – latex mixtures showed predisposition to gel with latex over 3–6 month timescale. Epoxysilane modification improves stability of Silica NPs on storage with waterborne latex at all pH values. Incorporation of Silica NPs into commercial latex formulation changes surface properties of coating and reduced dirt pickup of exterior masonry by over 50%.